Pengaruh Budaya Kerja Terhadap Perilaku Kerja Karyawan PT. Buana Citra Abadi - widayat, prama (Jurnal Daya Saing, 2016)
This study aims to identify and explain the influence of corporate culture on work behavior.The method used in this study is a survey of 51 employees at PT. Buana Citra Abadi Branch Dumai, Pekanbaru, Jambi and Palembang with sampling technique was conducted by sampling area. The results showed that the culture of work, and not significant positive effect on the behavior of the work, because there are many other factors that influence not described / examined in this study. Keywords: Culture Work and Work Behavior